Strategi Kesantunan Berbahasa dalam Film Gara-Gara Warisan - Zhafirah Amaliavanti; Badriyah Wulandari (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
A movie, as a literary work in the form of an audio-visual medium, is a dialogue-driven depiction of everyday life. In a movie, dialogue consists of utterances with a function, allowing characters to express themselves and convey a message. The purpose of the politeness strategy in the language is to facilitate the delivery of messages without harming the speaking partner's face. Therefore, the objective of this study is to discover and describe language politeness strategies in the Gara-Gara Warisan movie. This study employs a descriptive-qualitative methodology. While the approach in this study is the listening method and the advanced techniques, namely The Free Conversation Listening Technique (SBLC). Furthermore, the techniques used are transcript techniques and note-taking techniques. This study indicated that the most prevalent politeness approach is a positive politeness strategy and without utilizing any strategy (bald-on-record strategy), as opposed to a negative politeness strategy and an off-record politeness strategy.